Sensorineural Hearing Loss in Selective Immunglobulin A Deficiency - Erkan Eşki; Belgin Emine Usta; Suna Asilsoy; İsmail Yılmaz (Turkish Archives of Otorhinolaryngology, 2017)

(untitled)
Objective: To assess hearing functions in pediatric patients with selective immunoglobulin A (IgA) deficiency (SIGAD).Methods: Pure-tone audiometry, acoustic impedance, otoacoustic emission, and brainstem audiometric measurements were taken during a non-infectious period in 28 patients with SIGAD and 28 healthy children with normal otoscopic examination. The results of the hearing tests were compared between the two groups.Results: Two male patients and one female patient in the SIGAD group were found to have sensorineural hearing loss (SNHL). However, a comparison of the average pure tone cut-off values at 0.5, 1, 2, and 4 kHz did not reveal any statistically significant difference between the groups (p>0.05).Conclusion: Pediatric patients with SIGAD may exhibit SNHL at certain frequencies and require follow-up for the potential development of hearing loss.